Synergistic effects of blood flow restriction training and beetroot juice supplementation on knee extensor strength and fatigue resistance in college athletes - Yang, Xudong; Lu, Yue; Xu, Hongqi; Liu, Qing; Yun, Dae Hyun; Moon, Young Jin; Quan, Helong; Lee, Sang Ki (Biology of Sport, 2025)
Combining beetroot juice (BRJ) supplementation with blood flow restriction (BFR) training shows potential to meet the dual demand for enhanced muscle strength and improved fatigue resistance. This study involved 21 male college athletes who were randomized to a BFR group ( n = 10) and a BFR-supplemented BRJ group ( n = 11, nitrate 8 mmol/day) for 4 weeks of isokinetic BFR training. The strength (at 60°/s, 180°/s, and maximal voluntary isometric contraction) and fatigue resistance of the knee extensors and flexors were assessed pre- and post-intervention using an isokinetic dynamometer and a 30-second anaerobic power test, respectively. The four-week BFR and BFR+BRJ interventions significantly ( P < 0.05) improved knee extensor/flexor peak torque and power (at 60°/s and 180°/s), while also delaying the decline in knee extensor torque during the 100-repetition maximal voluntary contraction test. The BFR+BRJ group showed a more significant advantage in the second half of the contraction (51–100 repetitions; P < 0.01). In addition, both interventions significantly reduced the rate of decline in peak torque, peak power, and average power at 60°/s and 180°/s after fatigue, with the reductions being more pronounced in the BFR+BRJ group ( P < 0.01). In the anaerobic power test, the BFR+BRJ group maintained a higher power output for a longer duration ( P < 0.05)compared to before the intervention, whereasthe improvement in the BFR group was limited to the initial 3–10 seconds ( P < 0.05). The results suggest that BFR combined with BRJ is an effective training method for improving knee extensor strength performance and fatigue resistance.